China Ambition Through Digital Silk Road and Its Impact to Indonesia - Hizra Marisa (JOELS: Journal of Election and Leadership, 2025)
Focusing on the Digital Silk Road (DSR) initiative, this study analyzes the China's ambition through DSR and its impact to Indonesia, particularly in developing digital connectivity in Indonesia. DSR is often viewed as China's strategy to expand geopolitical influence and strengthen its authoritarian governance model through collaboration in the digital field. This study uses the theory of cooperation and cyber diplomacy as an analytical framework to understand the dynamics of this bilateral relationship. Through this theoretical lens, it will examine how China, with its ambition to become a "cyber superpower", manifests its aggressiveness in digital cooperation with Indonesia. This study will identify emerging patterns of cooperation, including digital infrastructure investment, technology transfer, and cyber capacity building. In addition, it will analyze various challenges in developing digital connectivity in Indonesia, such as issues of cybersecurity, data privacy, technological dependency, and potential impacts on digital sovereignty. Thus, this research offers an initial insight into the complexities and implications of China-Indonesia cooperation in the context of DSR, and how it shapes Indonesia's digital landscape.